Moxidectin as an Endectocide in Reindeer - Oksanen, A. (Acta Vet Scand, 1998)
During the winter 1991–92, 42 reindeer hinds of the Kaamanen Experimental Reindeer Herd in Finnish Lapland, naturally infected with various parasites, were allocated to 3 groups. One group was an untreated control group and the other 2 groups received either moxidectin or ivermectin at a dose of 200 µg kg(−1) subcutaneously. The efficacy of treatment was followed with monthly faecal examinations for nematode eggs and counting of warbles, Hypoderma tarandi larvae, and throat bots, Cephenemyia trompe larvae, from live animals in spring. The efficacy of moxidectin against warbles (92.8%) and throat bots (70.8%) did not match that of ivermectin, which was 100% against both species. Both moxidectin and ivermectin were effective against gastrointestinal trichostrongylid egg production over the December to May trial period indicating good efficacy against adult and inhibited trichostrongylids. Only non-significant differences were seen in weight development and calf birth weights between the groups. Because of its only moderate insecticidal efficacy, moxidectin cannot be recommended as an endectocide in reindeer.